2021
DOI: 10.1136/jitc-2021-002718
|View full text |Cite
|
Sign up to set email alerts
|

On-treatment immune prognostic score for patients with relapsed and/or metastatic head and neck squamous cell carcinoma treated with immunotherapy

Abstract: BackgroundPrevious studies have suggested that inflammatory markers (neutrophil-to-lymphocyte ratio (NLR), lactate dehydrogenase (LDH) and fibrinogen) are prognostic biomarkers in patients with a variety of solid cancers, including those treated with immune checkpoint inhibitors (ICIs). We aimed to develop a model that predicts response and survival in patients with relapsed and/or metastatic (R/M) head and neck squamous cell carcinoma (HNSCC) treated with immunotherapy.MethodsAnalysis of 100 consecutive patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…We screened the titles and abstracts of these studies and identified 24 potentially eligible studies. The full‐text versions of these 24 studies were then inspected according to the exclusion criteria, with 14 studies involving 929 patients determined to be eligible for inclusion in the present study 5,13–24 (Table 1). Two studies 15,23 contained overlapping data.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We screened the titles and abstracts of these studies and identified 24 potentially eligible studies. The full‐text versions of these 24 studies were then inspected according to the exclusion criteria, with 14 studies involving 929 patients determined to be eligible for inclusion in the present study 5,13–24 (Table 1). Two studies 15,23 contained overlapping data.…”
Section: Resultsmentioning
confidence: 99%
“…The HRs for OS were reported in 11 studies comprising 710 patients 5,13,14,17–21,23–25 and ranged from 0.86 to 5.04. The pooled analysis results are shown in Figure 3A.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, KEGG pathway analysis indicated that METTL3-related differentially expressed genes were involved not only in common oncogenic pathways but also in immune pathways. Several studies have con rmed the characterization of the immune microenvironment involved in the occurrence and development of HNSCC [34][35][36][37]. Studies have shown that the risk score composed of the m 6 A gene is related to the in ltration of dendritic cells, neutrophils, CD4 + T cells, CD8 + T cells, and B cells, and upregulated m 6 A regulators are positively correlated with PD-L1 in the HNSCC tumor immune microenvironment [38].…”
Section: Discussionmentioning
confidence: 99%